2017
DOI: 10.1186/s13054-016-1595-8
|View full text |Cite|
|
Sign up to set email alerts
|

Can calculation of energy expenditure based on CO2 measurements replace indirect calorimetry?

Abstract: BackgroundMethods to calculate energy expenditure (EE) based on CO2 measurements (EEVCO2) have been proposed as a surrogate to indirect calorimetry. This study aimed at evaluating whether EEVCO2 could be considered as an alternative to EE measured by indirect calorimetry.MethodsIndirect calorimetry measurements conducted for clinical purposes on 278 mechanically ventilated ICU patients were retrospectively analyzed. EEVCO2 was calculated by a converted Weir’s equation using CO2 consumption (VCO2) measured by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 27 publications
2
37
1
3
Order By: Relevance
“…EEVCO 2 = 3.941 × VCO 2 (L/min) / respiratory quotient + 1.11 × VCO 2 (L/min) × 1440. The respiratory quotient was considered to be a fixed value of 0.86 [14][15][16]. The mechanical ventilator measured the VCO2 (Hamilton-S1, Hamilton Medical AG, Bonaduz, Switzerland), and every minute, data are automatically sent to our electronic patient data management system (MetaVision; iMDsoft MetaVision®, Tel Aviv, Israel).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…EEVCO 2 = 3.941 × VCO 2 (L/min) / respiratory quotient + 1.11 × VCO 2 (L/min) × 1440. The respiratory quotient was considered to be a fixed value of 0.86 [14][15][16]. The mechanical ventilator measured the VCO2 (Hamilton-S1, Hamilton Medical AG, Bonaduz, Switzerland), and every minute, data are automatically sent to our electronic patient data management system (MetaVision; iMDsoft MetaVision®, Tel Aviv, Israel).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Many mechanical ventilators can measure VCO2, which in turn can be used to calculate EE using Weir's formula by assuming the respiratory quotient (RQ). This method remains controversial; Rousing et al concluded that VCO2-based calorimetry is an accurate alternative to predictive equations with a 10% accuracy rate of 89% compared to IC [31], whereas Oshima et al found end-expiratory VCO2 (EEVCO2) to be insufficiently accurate, with a 10% accuracy rate of 77% compared to IC [32]. It is important to note that EEVCO2 requires the use of a constant estimated RQ value; most studies use an RQ value of 0.85.…”
Section: The Use Of Indirect Calorimetrymentioning
confidence: 99%
“…×èñëåíí³ ìåòààíàë³çè ïîêàçàëè íèçüêå çíà÷åííÿ ïðîãíîñòè÷íèõ ð³âíÿíü [119,120], âàð³àáåëüí³ñòü ÿêèõ çá³ëüøóºòüñÿ, îñê³ëüêè ìàñà ò³ëà çàëèøàºòüñÿ çíà÷åííÿì, ÿêå âàaeêî òî÷íî îö³íèòè [121]. ßêùî íåïðÿìà êàëîðè-ìåòð³ÿ íåäîñòóïíà, òî ðîçðàõóíîê ÂÅÑ ç VCO 2 , îòðèìàíîãî ëèøå ç àïàðàòó øòó÷íî¿ âåíòèëÿö³¿ ëåãåí³â (ÂÅÑ = VCO 2 × 8,19), ïðîäåìîíñòðóâàâ á³ëüøó òî÷í³ñòü, í³ae ð³âíÿííÿ [122], àëå ìåíøó, í³ae ìåòîä íåïðÿìî¿ êàëîðèìåò𳿠[123]. Òàêîae ìîaeíà âèêîðèñòîâóâàòè VO 2 , âèðàõóâàíå ç êàòåòåðà ëåãåíåâî¿ àðòåð³¿.…”
Section: êë³í³÷íå ïèòàííÿ 8: ßê âèçíà÷èòè âèòðàòè åíåð㳿 (âå)?unclassified